Pond suspension sea cucumber seedling ecological temporary rearing method - AO ZHIHUI (2016)
The invention disclose a pond suspension sea cucumber seedling ecological temporary rearing method. A framework float cylinder cage is formed by an annular cylinder cage supporting plate, a sealed plastic pipe, a cylindrical netting and a stringing connection rope. The cylinder cage can produce certain buoyancy in seawater. Floating net sheets are threaded into a string bolt of a buoy via a lifting rope to be assembled into the cylinder cage; two ends of the string bolt are tied to the annular cylinder cage supporting plate; then sea cucumber seedlings are assembled to the framework float cylinder cage; when the framework cylinder cage is transversely placed on the bottom of a pond, the cylinder cages are connected to a row when the connection rope is tightened; a dropstone is arranged between each cylinder cage; with an adjustment of the length of the connection rope, a distance between the cylinder cage and the bottom of the pond and a cylinder cage transversely-arranged device is formed; when the cylinder cages are vertically arranged, a dropstone cylinder cage is installed on the bottom of each cylinder cage; the tops of the dropstone cylinder cages are connected to form a row when the connection rope is tightened; a cylinder cage vertically-arranged device is formed; and the cylinder cage is suspended in the pond. The beneficial effects of the pond suspension sea cucumber seedling ecological temporary rearing method are that the pond water body can be fully and rationally utilized and mu yield can be improved.